Ammonia Oxidation by the Arctic Terrestrial Thaumarchaeote Candidatus Nitrosocosmicus arcticus Is Stimulated by Increasing Temperatures - Alves, Ricardo J. Eloy; Kerou, Melina; Zappe, Anna; Bittner, Romana; Abby, Sophie S.; Schmidt, Heiko A.; Pfeifer, Kevin; Schleper, Christa (Frontiers in Microbiology, 2019)
Climate change is causing arctic regions to warm disproportionally faster than those at lower latitudes, leading to alterations in carbon and nitrogen cycling, and potentially higher greenhouse gas emissions. It is thus increasingly important to better characterize the microorganisms driving arctic biogeochemical processes and their potential responses to changing conditions. Here, we describe a novel thaumarchaeon enriched from an arctic soil, Candidatus Nitrosocosmicus arcticus strain Kfb, which has been maintained for seven years in stable laboratory enrichment cultures as an aerobic ammonia oxidizer, with ammonium or urea as substrates. Genomic analyses show that this organism harbors all genes involved in ammonia oxidation and in carbon fixation via the 3-hydroxypropionate/4-hydroxybutyrate cycle, characteristic of all AOA, as well as the capability for urea utilization and potentially also for heterotrophic metabolism, similar to other AOA. Ca. N. arcticus oxidizes ammonia optimally between 20 and 28°C, well above average temperatures in its native high arctic environment (−13–4°C). Ammonia oxidation rates were nevertheless much lower than those of most cultivated mesophilic AOA (20–45°C). Intriguingly, we repeatedly observed apparent faster growth rates (based on marker gene counts) at lower temperatures (4–8°C) but without detectable nitrite production. Together with potential metabolisms predicted from its genome content, these observations indicate that Ca. N. arcticus is not a strict chemolithotrophic ammonia oxidizer and add to cumulating evidence for a greater metabolic and physiological versatility of AOA. The physiology of Ca. N. arcticus suggests that increasing temperatures might drastically affect nitrification in arctic soils by stimulating archaeal ammonia oxidation.